TRANSPORMASI PENDIDIKAN BUDI PEKERTI DALAM PENINGKATAN MUTU SUMBER DAYA HINDU YANG BERKUALITAS - Temon Astawa, I Nyoman (LPM IHDN Denpasar, 2016)
The character education refers to the efforst to bring up the children to be mature with good ethics and morales. In Hindu, the education is setting the foundation, orientation, and perspectives that could be used mentally and spiritually for the character building. The mental toughness is related to the intelectuality as well as the personality that could avoid negativity and keep on progressing and understanding the tests of life. Spirituality is related to the belief in God, developing the devotion to Him, and taking any works as a service to Him. With these all Hindus may always do good deeds and compete through ages.